Methodological considerations for the assessment of postural stability and lower limb bilateral asymmetry - JORDAN GROOM (2023)
Purpose: There are currently no agreed methods for the assessment of postural stability using centre of pressure (CoP) analysis of quiet standing nor assessment of lower limb bilateral asymmetry measured during a countermovement jump (CMJ). Much of the existing literature surrounding both of these biomechanical assessments are varied and inconclusive in the determination of a criterion methodology. There is also a dearth of information regarding the reliability of both measures or expected outcomes. Therefore, the purpose of the current study was twofold. Firstly, to assess the methodology and reliability of postural stability measures obtained from a force-platform. Secondly, to investigate the methodology and reliability of measuring lower limb bilateral asymmetry using a dual-force-platform set-up. Methodology: Using a repeated measures design of test-retest reliability, postural stability and CMJ performance was assessed for male (n = 10, age = 32.7 ± 9.5 yrs., height = 1.797 ± 0.060 m, mass = 88.2 ± 14.4 kg) and female (n = 9, age = 32.4 ± 8.7 yrs., height = 1.662 ± 0.055 m, mass = 70.8 ± 13.5 kg) recreationally active individuals divided into three populations, female-only (FEM), male-only (MALE) and combined (ALL). For postural stability measurement, path length (Lp), sway area (As) and mean velocity (Vm) were reported from 8 trials for six epochs derived from 100 s of quiet standing. Four trials of each condition, were conducted on each of the two separate testing days. Reliability of bilateral CMJ performance was assessed from ten maximal CMJ trials using five kinetic and two temporal neuromuscular variables: peak force (Fmax), impulse due to eccentric and concentric contraction (Jecc and Jcon), peak instantaneous mechanical power (PPO), take-off velocity (Vto), percentage of jump duration that changeover from eccentric to concentric phases occurs (tecN) and percentage of jump duration that peak force occurs (tFmaxN). Lower limb bilateral asymmetry was then calculated for Fmax, Jecc, Jcon and tFmaxN using two SIs; sided, left leg vs right leg (LvsR) and un-sided, higher vs lower limb value (HvsL) to give asymmetry irrespective of limb side. Differences between conditions and SI methods were identified using paired-samples t-tests and test-retest reliability was assessed using ICC and Bland and Altman (B&A) plot analysis. Postural Stability Results: Lp and Vm were significantly higher (p ≤ 0.05) in the EC condition for all epochs. As demonstrated differences between the two conditions, however, not always significant; in all cases of significance, As was greater in the EC condition. Absolute ICC values for Lp and Vm were indicative of excellent reliability (>0.90) however, 95% CI ranged from poor (< 0.50) to excellent. As was the least reliable variable with regards to ICC 95% CIs, although absolute ICC values were still good (>0.75) to excellent across conditions and epochs. B&A plot analysis showed As was the most variable. In general, results showed that EC had the higher test-retest reliability, however differences between ICC values and the magnitude of the bias and LOA between conditions were small. It was not clear which epoch provided the most, or least, reliable results for Lp or Vm. For As, the 1st 30 s had the most variability, while for all variables, 90 s was one of the most reliable epochs. Cumulative moving average analysis showed a trend toward increased precision as number of repetitions increased for all epochs. Bilateral Asymmetry Results: Kinematic variables derived from analysis of a CMJ resulted in high test-retest reliability and agreement (ICC > 0.9) for Fmax, Jecc, Jcon, PPO, Vto and tecN. LvsR and HvsL methods of SI calculation were significantly different (p ≤ 0.05) for 3/4 variables. Fmax (ALL: LvsR - 0.72 ± 6.96%, HvsL 6.22 ± 3.89%), Jecc (ALL: LvsR 4.99 ± 23.47%, HvsL 25.29 ± 12.33%), Jcon (ALL: LvsR -6.93 ± 26.87%, HvsL 25.47 ± 13.80%), tFmaxN (ALL: LvsR -2.10 ± 7.87%, HvsL 5.67 ± 6.83%). Overall, the absolute ICCs of Jecc and tFmaxN ranged from poor to excellent, while Fmax and Jcon showed better agreement, although 95% CI ranges and magnitude of B&A LOAs were still large, particularly in LvsR (e.g., Fmax, ALL LvsR: Bias = 32%, LOA = 352%). B&A plot analysis demonstrated far smaller bias and LOA in HvsL than LvsR for all variables and populations. In both postural stability and bilateral asymmetry, there was no substantial differences noted between the reliability of FEM and MALE populations. For both cases, greater reliability could be seen for the majority of variables when FEM and MALE were combined in the ALL population. Conclusions: Lp and Vm had better reliability and lower variability than As. As is not recommended as a reliable postural stability performance parameter. There was a significant difference between visual conditions, indicating the impact of visual acuity on human postural control. Both EO and EC showed good reliability for all epochs, although B&A plots revealed variability in the data that should be considered in future research. Although EC appeared to be the slightly more reliable condition, it cannot be recommended over EO as they are representative of different requirements of human postural control. Bilateral CMJ performance showed good test-retest reliability, however, normalised temporal variables should be used with caution; tFmaxN was the least reliable variable. LvsR and HvsL methods of SI calculation were significantly different and have the ability to quantify very different inherent characteristics of bilateral CMJ performance. Results identify the importance of determining a suitable set of reference values and the consideration of the directionality of asymmetries on an individual basis. In a bilateral CMJ, the differences in the force generating capacity between limbs does not necessarily determine the variation in the magnitude of VGRF generated during the jump. Instead, variations in VGRF symmetry should be considered to represent bilateral variations in limb loading that stem from differing jumping and compensatory strategies adopted by individuals.